Rola organizacji przedsiębiorców w sferze zamówień publicznych - Przeszło, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Organisations of entrepreneurs may also participate in public procurement. Such organisations operating in Poland have a diverse legal character. These are in particular professional self-government organisations, chambers of commerce and other associations. According to the Public Procure-ment Law, they are entitled to bring legal protection measures for the members of these organisa-tions. It is worth noting, however, that provisions of law shaping the status of business organisations allow them to participate directly in public procurement as contractors. The basis for this is their legal personality and hence the opportunity to conduct business, if its subject corresponds to the statutory subject of public procurement.
Keywords: business organizations; legal protection measures; public procurement; legal personality; business activity; contractors